2018
DOI: 10.5388/aon.2018.18.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Posttraumatic Growth in Cancer Survivors

Abstract: 연구의 필요성우리나라에서Purpose: The purpose of this study was to identify the level of post-traumatic growth (PTG) and the factors affecting the PTG of cancer survivors. Methods: Data were collected from 147 cancer patients who were admitted to hospital to two hospitals, P and B city during July and September, 2017 using the PTG Inventory, Multidimensional Scale Perceived Social Support, Event-Related Rumination Inventory, Korean Cancer Coping Questionnaire, Resilience Scale, and Self-Esteem Scale. Data were analyzed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…It acts as a buffer in dealing with stresses coming from daily life or unexpected situations. PTG was found to improve the quality of life with better relationships, decreased depression or suicidal ideation, and increased willingness to participate in health‐promoting activities (Frazier et al, 2001; Park et al, 2018; Yu et al, 2010). Therefore, there is a need to help ICU nurses proceed to PTG achievement, rather than let them proceed in a psychopathological direction, to improve the quality of patients' care as well as the mental health of ICU nurses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It acts as a buffer in dealing with stresses coming from daily life or unexpected situations. PTG was found to improve the quality of life with better relationships, decreased depression or suicidal ideation, and increased willingness to participate in health‐promoting activities (Frazier et al, 2001; Park et al, 2018; Yu et al, 2010). Therefore, there is a need to help ICU nurses proceed to PTG achievement, rather than let them proceed in a psychopathological direction, to improve the quality of patients' care as well as the mental health of ICU nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous PTG studies were conducted for cancer patients (Park et al, 2018), natural disaster survivors (Yu et al, 2010), and sexual assault victims (Frazier et al, 2001). However, there have been few studies exploring predictors of PTG of ICU nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Social support can provide individuals with resources to cope with traumatic events, which can make it easier for patients to eliminate trauma-relayed cues. A previous study (50) showed that patients with lower social support were more likely to experience intrusive rumination. Intrusive rumination is considered as a negative coping style, which makes it difficult for patients to find positive meaning in trauma events (51), further affecting their spiritual well-being.…”
Section: Discussionmentioning
confidence: 91%
“…In terms of the time of diagnosis, 23.1% of cases in Class 1 been diagnosed for more than 5 years, but this was true for only 6.6% of cases in Class 2. In general, long-term survivors of more than five years are considered as "cured" from the prevailing medical point of view because they have overcome the physical and psychological burden caused by disease and treatment to some extent and have adapted to a new situation [31]. This suggests that it is important to actively implement follow-up management within five years.…”
Section: Discussionmentioning
confidence: 99%